The Double Slit Experiment:Particle or Wave? (or both?) - Papadopoulos, Omiros (Open Schools Journal for Open Science, 2026)
Name: Omiros (Homer) Papadopoulos Title: The Double Slit Experiment: Particle or Wave? (Or both?) Abstract: One of the most famous and oldest Quantum Physics experiments, the double slit experiment, demonstrated that light acts both as particles, as well as waves. First executed in 1801 by Thomas Young, it additionally proved that other particles can act in the same way, and played a vital role in the development of Particle physics. This presentation will explain both the science behind it, as well as featuring a demonstration of the experiment itself. The Presentation involves a theoretical segment and a practical segment, where the experiment is demonstrated.